Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1523/jneurosci.17-13-04994.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Increases GABA Release by Inhibiting a Resting K+Conductance in Hippocampal Interneurons

Abstract: Cholecystokinin (CCK) is found co-localized with the inhibitory neurotransmitter GABA in interneurons of the hippocampus. Also, CCK receptors are found in abundance in this brain region. The possibility that CCK alters interneuron activity was examined using whole-cell current-and voltage-clamp recordings from visualized interneurons in the stratum radiatum of area CA1 in rat hippocampal slices. The effect of CCK on GABA-mediated IPSCs was also determined in pyramidal neurons. The sulfated octapeptide CCK-8S i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 50 publications
11
59
1
Order By: Relevance
“…This finding is similar to observations by Miller et al (1997), who observed no effect of CCK on passive membrane properties of pyramidal cells. However, Miller et al, (1997) did not observe an effect of CCK on the AHP, while others (e.g. Dodd and Kelly, 1979;Shinohara and Kawasaki, 1997) reported the AHP reduction that we see.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is similar to observations by Miller et al (1997), who observed no effect of CCK on passive membrane properties of pyramidal cells. However, Miller et al, (1997) did not observe an effect of CCK on the AHP, while others (e.g. Dodd and Kelly, 1979;Shinohara and Kawasaki, 1997) reported the AHP reduction that we see.…”
Section: Resultssupporting
confidence: 92%
“…Hence, although the agonist does reduce the AHP, the pyramidal cell passive properties are insensitive to CCK8-S. This finding is similar to observations by Miller et al (1997), who observed no effect of CCK on passive membrane properties of pyramidal cells. However, Miller et al, (1997) did not observe an effect of CCK on the AHP, while others (e.g.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The anatomical distribution of CCK-containing neurons in the hippocampus suggests that CCK is involved in both afferent and main efferent hippocampal pathways (Greenwood et al 1981), and a recent electrophysiological study has shown that CCK increases GABA release by inhibiting a resting K ϩ conductance in hippocampal interneurons, thus leading to an increased tonic inhibition of pyramidal neurons (Miller et al 1997).…”
Section: Rtms Differentially Affects the Expression Of The Modulatorymentioning
confidence: 99%